2020
DOI: 10.1109/access.2020.3008721
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Routing Orchestration for Ultra-Low Latency Transport Networks

Abstract: Autonomous driving scenarios face the need for millisecond real-time response, which has led to the study of mobile networks with high speed and ultra-low latency. Software-defined networking (SDN) is recognized as a key technology for next-generation networks because it contains advanced functions such as centralized control, software-based traffic analysis, and forwarding rules for dynamic updates. In this paper, an SDN with flexible architecture is considered and a transport component is proposed. The compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The suggested method is highly accurate at determining the appropriate path combinations. The author in [42] analyses the effect of route prediction on the performance of the transport network. In order to effectively perform fast inference and lower the cost of control information exchange, the central controller uses a DNN classifier to predict the path sequence.…”
Section: Imitation Learning Based Routing Algorithmmentioning
confidence: 99%
“…The suggested method is highly accurate at determining the appropriate path combinations. The author in [42] analyses the effect of route prediction on the performance of the transport network. In order to effectively perform fast inference and lower the cost of control information exchange, the central controller uses a DNN classifier to predict the path sequence.…”
Section: Imitation Learning Based Routing Algorithmmentioning
confidence: 99%
“…State-of-the-art activities on reducing E2E delay in cellular CNs include optimization-based approaches [19,20] and customized transport layer protocols [21,22]. Qu et al in [19] suggested a dynamic flow migration strategy in 5G CNs with constrained resources for delay-sensitive services.…”
Section: Related Workmentioning
confidence: 99%
“…Results proved that their transport protocol could achieve a lower E2E delay when compared to the conventional transport layer protocol. [22] proposed an SDN‐based architecture and a transport protocol for reducing latency. Their proposed path selection algorithm could outperform the open shortest path first (OSPF) approach.…”
Section: System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, the part can receive a product characterized stream access control procedure that incorporates an allinclusive sending component (retransmission) to improve the transient reaction execution. At that point the effect of route forecast on transport network execution is finished by utilizing offline preparing and prediction [10]. QoS mindful organization design and multipath sending approach was acquainted all together with deal with the SDN activity empowered Open Virtual Switches (OVSs).…”
Section: Related Workmentioning
confidence: 99%